Judex Facti Consistency in Imposing Theft with Weights: A Review of Cassation Decision Number 1585 K/Pid/2025 - Sitompul, Ariman; Bayu Dwi Arya, Muhammad (International Asia Of Law and Money Laundering (IAML), 2025)
This study examines in depth the consistency of judex facti in the application of Article 363 Paragraph (1) 3 of the Criminal Code related to theft with weighting based on Cassation decision number 1585 K/Pid/2025. The focus of the study is directed not only to the appropriateness of the application of material and formal legal norms, but also to the correctness of Juridical considerations, the objectivity of the assessment of facts, as well as the harmonization of decisions between the District Court, the High Court and the Supreme Court. Through normative legal research methods with statute approach, conceptual approach, and case approach, this research explores how the structure of legal considerations is built at each judicial level and how the quality of legal reasoning affects the final decision.The results showed that the Supreme Court expressly upheld the application of the law by judex facti, especially in terms of proving the element of entering the house at night without permission and taking goods that are carried out when the owner is sleeping, so that all elements of Article 363 Paragraph (1) 3 of the Criminal Code are fulfilled. The Supreme Court also considered that the imposition of a criminal sentence of 10 months in prison by the District Court and which was reinforced by the High Court was in accordance with the provisions of Article 197 Paragraph (1) letter f of the Criminal Procedure Code, because the judges of First Instance and appeal had proportionately considered the aggravating and mitigating circumstances of the defendant.This study also found that the public prosecutor's objection in the Cassation application, which basically questioned the severity of the crime, it cannot be justified according to law because the assessment is the domain of judex facti authority and does not include Cassation grounds as stipulated in Article 253 Paragraph (1) of the Criminal Procedure Code. Thus, the Supreme Court reaffirmed the fundamental principle that Cassation only checks the application of the law, not corrects the appreciation of facts or the degree of conviction, unless there is a real error.Overall, this study confirms the importance of consistency in the application of law between judex facti and judex juris to maintain legal certainty, substantive justice, and the credibility of the criminal justice system. Consistency is a crucial element in forming decisions that are not only formally valid, but also morally and rationally legitimate. Therefore, this Cassation ruling is a concrete example of how the Supreme Court exercises the function of judicial supervision (judicial control) within the limits of its authority without intervening in the discretionary space of judges of First Instance and appeal.